1982
DOI: 10.1121/1.2019198
|View full text |Cite
|
Sign up to set email alerts
|

The perceptual reality of tone chroma in early infancy

Abstract: In the framework of a habituation-recovery paradigm, we presented 40 infants, aged 70–110 days, two cyclically repeating melodic sequences of pure tones. The habituation sequence, A B C A B C …, was the same for all infants; its component tones, A, B, and C, had a level of 80 dB SPL and respective frequencies of 736.7, 487.4, and 428.1 Hz. B and C were replaced by X and Y in the test sequence, A X Y A X Y …, which had three different versions, heard by three separate groups of infants. For each group, X and Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…At 11 months, 50% of a long melodic monologue represented notes from the F-major scale (particularly, F, A, C, D, F). The privileged position of the diatonic small ratios has been shown in developmental studies for octaves (Demany & Armand, 1984;Krumhansl & Jusczyk, 1990, as described by Krumhansl, 1990); the major triad , and other simple ratios (Schellenberg & Trainor, 1996;Trainor, 1997;Trainor & Trehub, 1993;Zentner & Kagan, 1996). They related difficulties with certain intervals to instability of the 7th and 11th harmonics (p. 199).…”
Section: Harmonic Relations Between Notesmentioning
confidence: 91%
“…At 11 months, 50% of a long melodic monologue represented notes from the F-major scale (particularly, F, A, C, D, F). The privileged position of the diatonic small ratios has been shown in developmental studies for octaves (Demany & Armand, 1984;Krumhansl & Jusczyk, 1990, as described by Krumhansl, 1990); the major triad , and other simple ratios (Schellenberg & Trainor, 1996;Trainor, 1997;Trainor & Trehub, 1993;Zentner & Kagan, 1996). They related difficulties with certain intervals to instability of the 7th and 11th harmonics (p. 199).…”
Section: Harmonic Relations Between Notesmentioning
confidence: 91%
“…One exception to this is the octave. Listeners seem more sensitive to deviations from the octave than to deviations from adjacent intervals, both for simultaneously [17] and sequentially [18,19] presented tones. The same method yields weak and inconsistent effects for other intervals [20], suggesting that the octave is unique in this regard.…”
Section: Relative Pitch – Behavioral Evidencementioning
confidence: 99%
“…Demany and Armand (1984) demonstrated that infants perceive tones an octave apart (standing in a 2:l ratio) to be more similar than tones slightly more than or slightly less than an octave apart. In the present study, we explored the possibility that simple frequency ratios in general have special status for young infants.…”
mentioning
confidence: 98%